Pengaruh Model Pembelajaran Scramble Terhadap Keaktifan Belajar PAK Siswa Di SMP Negeri 1 Harian Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Rido Widyawati Sianturi; Simion D Harianja; Risden Anakampun; Lasmaria Lumban Tobing; Frainskoy Rio Naibaho (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This research aims to determine the positive and significant influence of the Scramble Learning Model on the Learning Activeness of PAK Students at SMP Negeri 1 Harian Samosir Regency for the 2023/2024 Academic Year. With the hypothesis, there is a positive and significant influence between the Scramble Learning Model on the Active Learning of PAK Students at SMP Negeri 1 Harian Samosir Regency for the 2023/2024 Academic Year. The research population was 97 people and the research sample was 63 people. Data was collected using a closed questionnaire of 40 items which were compiled by researchers based on variable indicators in accordance with expert theory. The instrument trial was carried out on 30 students in class VIII and IX at SMP Negeri 2 Harian who had tested its validity and reliability. The results of data analysis show that the results of a simple linear equation are Y ̂=21.6+1.26x. The t test results show the value of tcount > ttable, namely 4.503 > 2.000. Next, data analysis for hypothesis testing with the f test obtained a value of Fcount > Ftable, namely 20.41>1.39, so it can be concluded that the hypothesis is accepted and based on the results of the coefficient of determination, the magnitude of the influence of the Scramble Learning Model on the Learning Activeness of PAK Students at SMP Negeri 1 Harian Regency is obtained. Samosir for the 2023/2024 Academic Year is 25% and another 75% is obtained from other factors.